Differential expression of miRNAs in Osborne's ligament of cubital tunnel syndrome - Zhou, Xian-Hu (Mol Med Rep, 2017)
Cubital tunnel syndrome (CuTS) is the second most common peripheral nerve compression disease, however, the pathogenesis and pathology of CuTS remain to be fully elucidated. The aim of the present study was to compare the expression pattern of microRNAs (miRNAs) in pachyntic Osborne's ligament with that in control tendinous tissue, and select meaningful miRNAs for further investigation of the clinical pathological mechanism underlying CuTS. A microarray assay was performed to examine the expression profiles of miRNAs in the Osborne's ligament and control tendinous tissues. An online bioinformatics algorithms tool (miRWalk) was used to predict putative target genes for the deregulated miRNAs, and functional annotation was performed by Gene Ontology (GO) enrichment and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis. Finally, the results of microarray were partially validated using reverse transcription-quantitative polymerase chain reaction analysis. The expression of total of 60 miRNAs were found to be significantly different between the pachyntic Osborne's ligament and control tendinous tissues. MiRWalk2.0 predicted 1,804 target genes for these miRNAs, and the GO functional analysis of the predicted genes suggested cellular mechanisms, including metabolic process, regulation of cell growth, cell cycle processes, cell division regulation, cellular metabolic process and signal transmission, were involved. Furthermore, KEGG pathway analysis revealed important pathways, including adherent junction, focal adhesion, lysine degradation, cell adhesion molecules and mitogen-activated protein kinase. Compared with the heathy tissue, Osborne's ligament tissue from patients with CuTS showed a markedly different miRNA expression profile, which suggested that miRNAs may be involved in the pathogenesis of CuTS.